Trolling in the framework of political practices - Santander Herrera, Rubén (2021)
In Chile, influential public figures are increasingly using the media to accuse social networks of being a danger to democracy and to characterize their users as intolerant and destructive. This essay defines that behavior, known as trolling, by delimiting its constitutive characteristics in order to situate the phenomenon as a political practice independent of an alleged trolling agenda, a particular subculture, a historical context or a specific technology. To give an account of the historical ubiquity of trolling, we used a journalistic text by Karl Marx. Based on Rancière’s (2006) conceptualization of politics and Fraser’s (1999) critique of Habermas, we maintain that the function of trolling is to give shape to an attempt to modify the distribution of what is sensitive by imposing new oppositions of terms, displacing or undermining the framework of a discourse. In this sense, trolling is a potentially emancipatory political practice. The purpose of this essay is not to evaluate trolling in ethical terms but to situate it regarding its uses, possibilities and relations, and to suggest criteria for judging it as an object that can be approached from the perspective of political communication.